2010
DOI: 10.1021/ol102495v
|View full text |Cite
|
Sign up to set email alerts
|

Dialkylaluminum N,O-Dimethylhydroxylamine Complex as a Reagent to Mask Reactive Carbonyl Groups in Situ from Nucleophiles

Abstract: Aluminum complexes of N,O-dimethylhydroxylamine are effective reagents to mask carbonyl groups in situ from nucleophilic addition by organolithiums, Grignard reagents, and borohydrides. The utility of this process by selectively adding nucleophiles into carbonyl groups on a variety of structures as well as distinguishing between carbonyl groups on a sensitive natural product is demonstrated. (1)H NMR analysis supports the in situ masking of the more reactive carbonyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In addition, transformations of the 5-oxoaldehyde derivative 1c to 2f and 2g in high yields (runs 6, 7) demonstrated that the method can be utilized in efficient routes for the construction of synthetically useful lactols. Aromatic aldehydes also participated in the selective in situ phosphonium salts protection process (runs [8][9][10][11][12][13]. Moreover, the use of Corey-Bakshi-Shibata (CBS) reagent enabled asymmetric reduction of a ketone in the presence of an aldehyde with good selectivity (run 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, transformations of the 5-oxoaldehyde derivative 1c to 2f and 2g in high yields (runs 6, 7) demonstrated that the method can be utilized in efficient routes for the construction of synthetically useful lactols. Aromatic aldehydes also participated in the selective in situ phosphonium salts protection process (runs [8][9][10][11][12][13]. Moreover, the use of Corey-Bakshi-Shibata (CBS) reagent enabled asymmetric reduction of a ketone in the presence of an aldehyde with good selectivity (run 9).…”
Section: Resultsmentioning
confidence: 99%
“…1) In contrast, multiple-step sequences, which include often complicated protection and deprotection steps, are required for selective conversion of less reactive carbonyl groups in substrates that also contain more reactive carbonyl moieties. Moreover, the few methods that have been devised to reverse the reactivity order of carbonyl groups [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have drawbacks that include low substrate scope and reactions that require strict stoichiometry control and use of expensive reagents. Thus, in spite of their ability to simplify preparative sequences, these methods have rarely been used in synthetic organic chemistry.…”
mentioning
confidence: 99%
“…Equation 1 of Chart 13 shows their strategy, and as optimization of conditions addition of i-PrMgCl before adding nucleophile gave the best result 18,19) (Chart 13, Eq. 2).…”
Section: Aluminum Amidementioning
confidence: 99%
“…There are several reports of such transformations using in situ protection methods, in which the more reactive carbonyl group is protected during the transformation of the less reactive carbonyl group, and then reformed during workup. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Additionally, there are several reports for reversing the reactivities of carbonyl functions in chemoselective catalytic reduction by using transition metals. 21,22) However, most of the reported methods have drawbacks, such as narrow substrate scopes, the need for strict stoichiometric control, and the use of expensive reagents; therefore, although they simplify the preparative sequences, these methods have rarely been used in synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%